Artificial reef to help preserve marine life ecosystem - Gan, Leong Ming
Tioman Island is known as one of the world’s 10 most beautiful islands and has a diversity of marine life including colourful reef. The island is an attraction, drawing local and foreign tourists who want to bask in the natural wonders it offers.